Internet of Things: Applications and Challenges - Mehta, Deepanshu (International Journal of Computer Sciences and Engineering, 2018)
Internet of Things (IoT) refers to the latest technology which is changing the way of looking towards the world. The terminology Internet of Things (IoT) refers to a future where every day physical objects are connected by the Internet in one form or the other, but technology is quickly changing the way we interact with the world around us. It is the advancements in the networking with the help of which real world objects can be connected to communicate with one another without human intervention. IoT envisions a future in which both digital and physical world can be linked, by means of appropriate information and technologies. IoT is supported by the wide range of distributed devices with embedded identification, sensing and/or actuation capabilities. In this paper will discuss the applications and challenges of Internet of Things (IoT).